2018
DOI: 10.1152/ajpgi.00411.2017
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-related differences in mucosa-associated microbiota and intestinal barrier function in colonic Crohn’s disease

Abstract: Crohn's disease (CD), characterized by discontinuous intestinal injury and inflammation, has been associated with changes in luminal microbial composition and impaired barrier function. The relationships between visual features of intestinal injury, permeability, and the mucosa-associated microbiota are unclear. Individuals undergoing routine colonoscopy (controls) and patients with CD were evaluated by clinical parameters and confocal laser scanning endomicroscopic colonoscopy (CLE). Patients with CD were cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 46 publications
3
37
0
Order By: Relevance
“…This may partially explain the enhanced expression of ZO-1 and claudin-1, since the overproduction of IL-6 and TNF-α was considered to participate in enhancing intestinal epithelial permeability [ 34 ]. Recent studies suggested that intestinal inflammation might be associated with microbial composition changes [ 20 ]. AUR can inhibit the growth of pathogenic bacteria like Escherichia-Shigella, which can cause intestinal inflammation through the activation of nuclear factor-κB (NF-κB) and mitogen-activated protein kinase (MAPK) signal pathways [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may partially explain the enhanced expression of ZO-1 and claudin-1, since the overproduction of IL-6 and TNF-α was considered to participate in enhancing intestinal epithelial permeability [ 34 ]. Recent studies suggested that intestinal inflammation might be associated with microbial composition changes [ 20 ]. AUR can inhibit the growth of pathogenic bacteria like Escherichia-Shigella, which can cause intestinal inflammation through the activation of nuclear factor-κB (NF-κB) and mitogen-activated protein kinase (MAPK) signal pathways [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, dietary supplementation of PCA increased the Firmicutes/Bacteroidetes ratio, in which Firmicutes are more effective as an energy source than Bacteroidetes in promoting more efficient absorption of calories [ 5 , 37 ]. Furthermore, the decrease in the phylum Firmicutes was also observed in Crohn’s disease patients [ 20 ], and Firmicutes are considered as one of the producers of short-chain fatty acid (SCFA) [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the determination of mucosal bacteria from injured sites of patients with CD show increased numbers of Escherichia (phylum Proteobacteria) but reduced proportions of Lachnospira , Faecalibacterium , and Blautia , all belonging to phylum Firmicutes, as compared to biopsies from adjacent mucosal sites without injury. The dysbiosis is suggested to favor or maintain endothelial lesions in CD [27]. Recently, a dysbiosis and invasion of bacteria has also been described in the gut of patients with ankylosing spondylitis.…”
Section: Host—microbiota Interactionmentioning
confidence: 99%
“…Blautia, involved in complex carbohydrate digestion, is recognized as a good indicator of the intestinal health, and its increase is bene cial. On the contrary, a Blautia reduction was observed in patients affected by heart failure [23], by hepatic and Chron's disease, and cancer [24][25][26]. Very interestingly, it has just been published that Blautia genus is inversely related with visceral fat accumulation [27].…”
Section: Discussionmentioning
confidence: 99%